Research on the Pin Fin Efficiency and Structure - Fan Bailin; Huang Ganghan; Xu Long; Wang Yanjun; Zhang Pei (Institute of Advanced Engineering and Science, 2013)
The performance of pin fin heat sink can be to measure through the temperature field. The temperature field and efficiency of the Pin Fin were analyzed, Pin fin efficiency curve was drowned also the distribution of the temperature field along the length of the pin fin curve was drawn. Thermal resistance was composed by thermal resistance of Aluminum substrate、 thermal resistance of convective heat transfer and the thermal resistance of the cooling liquid. The change rule was studied through the calculation on Aluminum plate thermal resistance、 thermal resistance of convective heat transfer and the thermal resistance of the cooling liquid. Its change regularity was simulated by toolbox In the MATLAB, and it was found that thermal resistance of convective heat transfer effect on the efficiency was most obvious in a certain amount of the heat and flow for thermal resistance of the Pin-fin radiator under the premise. The structural parameters of radiator were related to the size of thermal resistance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2688